Penilaian Kelas Kesesuaian Lahan Tanaman Kehutanan dan Pohon Serbaguna di Kecamatan Payung Kabupaten Karo (Land Suitability Evaluation of Forest Trees Species and Multi Purpose Trees Species in Payung Subdistrict, Karo Regency) - Heri Rizki Sitepu; Rahmawaty Rahmawaty; Abdul Rauf (Program studi Kehutanan USU, 2013)
Land suitability evaluation is activity comparing conditions required by land utilization type with characteristics or land quality owned by used land. The purpose of this research was to evaluate land suitability for forest trees species and multi purpose trees species in Payung Subdistrict Karo Regency. This research was conducted in four stages: 1) Research preparations, 2) Undertaking research in location, 3) Data processing, 4) Result presentation. The method of this research is matching system. Location has 10 land units. Land unit components were including slope, soil type and land cover. Actual land suitability for Mahogany and Pine dominantly are non suitable and for Ecalyptus, Durian and Avocado are marginal suitable. Potential land suitability for Mahogany and Pine have the same class as actual land suitability. It is because the resistor factor is permanently. Eucalyptus, Durian and Avocado have different land suitability as actual land suitability for some land units. It is because the resistor factor isn’t permanently. Keywords: Land Evaluation, Land Suitability, Land Unit